PEWARISAN PADA MASYARAKAT BATAK MANDAILING YANG MELAKUKAN PERKAWINAN DENGAN SUKU MINANGKABAU DI KECAMATAN PASAMAN KABUPATEN PASAMAN BARAT PROPINSI SUMATERA BARAT - , FADHIL ISLAMIE; , Agus Sudaryanto S.H.,M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The purpose of this research is to determine what factors are causing the occurrence of intermarriage between the Minangkabau tribes and Batak Mandailing tribe in subdistrict of Pasaman. In addition, also to know the laws of inheritance which is run in the community who perform mixed marriages between Batak Mandailing tribe and Minangkabau tribe in subdistrict of Pasaman. This research is descriptive analysis, which give an idea about the state of the object under study problems thoroughly and systematically on the basis of data obtained. The subjects consisted of respondents of 30 (thirty) people consisting of a mixed marriage couples are male and female Batak Mandailing tribes and Minangkabau tribes, also 10 (ten) pairs, couples of mixed marriages that women and men Batak Mandailing tribes and Minangkabau tribes 10 (ten) pairs , and 10 (ten) persons who had received inheritance from parents who married between ethnic Batak and Minangkabau. The sampling technique used was non-random sampling. Sampling was carried out by quota sampling. The approach used in empirical research is legal, then in drawing conclusions using inductive logic approach, which originated from the things that are special and then general conclusions drawn. The research result shows the factors caused intermarriage between the Batak Mandailing tribes and Minangkabau tribe in subdistrict Pasaman are environmental factors, religious factors, acculturation factors and partner factors. Inheritance law that is run on people who do intermarriage between ethnic Batak Mandailing and Minangkabau in District Pasaman generally uses a system of individual lineages of Customary Law, but some are using the system of inheritance under Islamic law with individual bilateral system.